The Construction of Algonquian Hunting Territories: Private Property as Moral Lesson, Policy Advocacy and Ethnographic Error. - Feit, Harvey A. (University of Wisconsin Press, Madison, see https://uwpress.wisc.edu/books/0339.htm, 1991)
The common sharp separation by anthropologists of ethnological and theoretical analysis from policy advocacy and other forms of applied anthropology has obscured and hidden their inseparability in anthropological histories, ethnology and theorizing. This chapter shows how the dispute within Americanist Anthropology about the kinds of property rights that constitute Algonquian family hunting territories requires attention to anthropologists’ policy advocacy. and it demonstrates some of the consequences of not considering them for ethnology, theory and disciplinary histories. Since the early 20th century there has been a debate focused on two opposing views of Algonquian land tenure. The dominant view in mid-century is that private property tenures were not found in Native American hunting societies before contact with Europeans and that Algonquian family hunting territories were the result of changes brought about by the fur trade. The other side of the debate was part of the Boasian critique of evolutionism and was based on Robert Lowie's use of Frank Speck's material in ‘Primitive Society’ (1920), Lowie's rejoinder to Lewis Henry Morgan's ‘Ancient Society’ (1877), the latter extensively used by Frederich Engels (1884). Anthropologists on both sides of the debate have assumed that Algonquian family hunting territories are an existing, or developing, form of private property. More recent fieldwork has shown that the tenure practices and concepts of northern Algonquians are not forms of private property, and that the view that they were was a shared ethnographic error. Why did both Speck and his critics construct their accounts of Algonquian hunting territories as if they conformed to notions of private property? In Speck’s case, examined in this chapter, his policy advocacy for Indian land rights (as he called them) stressed they were private property rights. Neither side analysed the historical context of the debate itself, or the roles of anthropological advocacy in its development. Even anthropologists who insisted that the development of family hunting territories could only be comprehended within a history of Indigenous colonization and economic change still saw the anthropological debates about hunting territories as an ideological-analytical dispute, and they did not analyse the active policy engagement-ethnography-theorizing of the anthropologists in the debate. This chapter explores these contexts, histories, and consequences.
This paper went through several versions over a number of years, and I benefitted from comments and suggestions by: Matthew Cooper, James Morrison, Colin Scott, George W. Stocking, Jr., and Bruce Trigger. Others who commented as participants in aspects of the history analysed here included: Eleanor Leacock, Edward S. Rogers, Clifton Amsbury, and Edmund Carpenter. I have returned to aspects of these issues in later papers, especially: in 2009 in “Histories of the Past, Histories of the Future: The Committed Anthropologies of Richard Slobodin, Frank G. Speck and Eleanor Leacock,” in A Kindly Scrutiny of Human Nature: Essays in Honour of Richard Slobodin, edited by Richard Preston, published by Wilfred Laurier University Press, Waterloo, Pp. 45-76; and in 2018 in “Dispossession with Possession, Governance with Colonialism: Algonquian Hunting Territories and Anthropology as Engaged Practice,” in Anthropologica 60: 149-160, available at: http://hdl.handle.net/11375/23928.
Keywords: History of Anthropology; Americanist Anthropology; Colonialism and Anthropology; Advocacy in Anthropology; Theory and Advocacy; Frank Speck; Lewis Henry Morgan; Marxism and Anti-Marxism; Algonquian Land Tenure